Development of Immunological Test Kit for the Detection of Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) in Swine - Surasak Jittavisutthikul; Amara Thongpan; Orawan Boodde; Wilairat Shumsing; Worawidh Wajjwalku (Agriculture and Natural Resources, 2008)
Two types of porcine reproductive and respiratory syndrome virus (PRRSV), European (EU) and North American (US), cause an important swine disease called porcine reproductive and respiratory syndrome (PRRS). An enzyme-linked immunosorbent assay (ELISA) for the simultaneous detection of serum antibodies against these two PRRS was developed. A fused protein containing EU PRRSV and US PRRSV nucleocapsid proteins (USEU-rN protein) expressed in Escherichia coli were partial purified and used as antigens. As determined by a checkerboard titration, an optimal dilution of the USEU-rN protein and serum were 1:1600 and 1:40, respectively. The optimal cut-off value for the developed USEU PRRS ELISA was 0.4, with diagnostic sensitivity and specificity of 97.5% and 100%, respectively. Using Two Graph-ROC program testing with 200 positive sera (IDEXX® HerdCheck PRRS ELISA) and with 200 negative sera from PRRS-free country (Denmark), comparison of 1,077 field sera obtained from USEU PRRS ELISA with those from IDEXX® ELISA showed the degree of agreement (k value) was highly obtained at 0.7916. The kit is considered reliable for routine diagnosis, epidemiological surveys and outbreak investigations.